(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The Ottonian period is considered the darkest moment in the history of the Abbey of Nonantola. Since the time of Girolamo Tiraboschi, the historiographical narrative has considered the appointment of the great bishops of Emilia as abbot as a disgrace for the monastic community and its wealth. It was not until the 11th century that the monastery regained its former splendour, thanks to the return of autonomous abbots. The paper examines the Nonantola archives for the whole of the 10th century, paying particular attention to the Ottonian diplomas granted to the abbey and its abbots. The aim is to place the developments at Nonantola in the wider context of the Kingdom of Italy in the second half of the 10th century, when vigorous instances of spiritual reform of great royal monasteries were combined with the Ottonian will to recover the fiscal component of these great monastic patrimonies at the disposal of the publicum.